2020
DOI: 10.3889/oamjms.2020.5494
|View full text |Cite
|
Sign up to set email alerts
|

Probiotics May Improve Serum Folate Availability in Pregnant Women: A Pilot Study

Abstract: BACKGROUND: Probiotics are living microorganisms that confer a health benefit when administered in adequate amounts. There is evidence in the current literature about the importance of probiotic use in pregnancy. The early supplementation of probiotics in the perinatal and postnatal periods seems to have a positive impact on the overall mother’s health and future health of infants. AIM: Our pilot study aimed to test the ability of specific probiotics strains in combination with the kiwi-unique enzyme act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

7
1

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 31 publications
1
8
0
Order By: Relevance
“…Except for oral hygiene, which helps maintain the physiological state of saliva, a balanced diet and supplements of non-pathogenic microorganisms must be used to keep the oral microbiota in the normal range [ 285 ]. These non-pathogenic microorganisms are named probiota, and by interacting with the intestinal microbiota, have given good results in various conditions and pathologies [ 259 , 265 , 286 , 287 , 288 , 289 , 290 ].…”
Section: Microbiota In Tissue Repair Processesmentioning
confidence: 99%
“…Except for oral hygiene, which helps maintain the physiological state of saliva, a balanced diet and supplements of non-pathogenic microorganisms must be used to keep the oral microbiota in the normal range [ 285 ]. These non-pathogenic microorganisms are named probiota, and by interacting with the intestinal microbiota, have given good results in various conditions and pathologies [ 259 , 265 , 286 , 287 , 288 , 289 , 290 ].…”
Section: Microbiota In Tissue Repair Processesmentioning
confidence: 99%
“…The studies in vitro showed a slow and prolonged release of resveratrol in the gastro-intestinal tract. The resveratrol shows good effects in inflammatory conditions (it reduces the production of nitric oxides), oncology (it reduces the release of free radicals), cardiovascular diseases (it protects the cell death induced by the reactive oxygen species ROS, by activating the AMP-activated protein kinase (AMPK) in the heart muscle cells (H9c2)), obesity, type 2 diabetes, and neurodegenerative diseases [ 198 , 199 , 200 , 201 , 202 , 203 , 204 ]. In particular, the capacity of the resveratrol to inhibit the growth of bacteria, fungi, and viruses has been widely studied.…”
Section: Resveratrol Adjuvant Supplements For Covid-19mentioning
confidence: 99%
“…Resveratrol is characterized by anti-inflammatory properties while, in cancer patients, it is able to decrease the effect of free radicals and, in subjects affected by cardiovascular diseases, it is able to inhibit the cell apoptosis induced by the reactive oxygen species ROS, activating the AMP-activated protein kinase (AMPK) in the heart muscle cells (H9c2) [203,[292][293][294][295]. Moreover, the resveratrol compounds are able to control obesity, type 2 diabetes, and neurodegenerative diseases [203,[292][293][294][295]. In fact, the inhibitory capability of resveratrol against bacteria, fungi, and viruses has been reported by several articles.…”
Section: Resveratrolmentioning
confidence: 99%